Rapid Construction of an Infectious Clone of the Zika Virus, Strain ZKC2 - Qin, Zhiran; Chen, Yangyang; Yu, Jianhai; He, Xiaoen; Liu, Xuling; Zhu, Li; Wu, Qinghua; Wan, Chengsong; Zhang, Bao; Zhao, Wei (Frontiers in Microbiology, 2021)
Zika virus (ZIKV) has had detrimental effects on global public health in recent years. This is because the management of the disease has been limited, in part because its pathogenic mechanisms are not yet completely understood. Infectious clones are an important tool that utilize reverse genetics; these can be used to modify the ZIKV genomic RNA at the DNA level. A homologous recombination clone was used to construct pWSK29, a low copy plasmid that contained sequences for a T7 promoter, the whole genome of ZIKV ZKC2 strain, and a hepatitis delta virus ribozyme (HDVr). High fidelity PCR was then used to amplify the T7 transcription template. The transcript was then transfected into susceptible cells via lipofection to recover the ZIKV ZKC2 strain (rZKC2). Finally, the virulence of rZKC2 was evaluated both in vitro and in vivo. The rZKC2 was successfully obtained and it showed the same virulence as its parent, the ZIKV ZKC2 strain (pZKC2), both in vitro and in vivo. The 3730 (NS2A-D62G) mutation site was identified as being important, since it had significant impacts on rZKC2 recovery. One of the earliest strains of ZIKV that was imported into China was used for infectious clone construction and one possible site for antiviral medication development was discovered. The use of homologous recombination clones, of PCR products as templates for T7 transcription, and of lipofection for large RNA transfection could increase the efficiency of infectious clone construction. Our infectious clone provides an effective tool which can be used to explore the life cycle and medical treatment of Zika virus.